ANALISIS KOMPOSISI ASAM LEMAK PADA MINYAK KELAPA FERMENTASI DAN MINYAK KELAPA TRADISIONAL - Fatma Al-Hamid; J Leiwakabessy; A Bandjar (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
Analysis of fatty acid in ferment coconut oil and traditional coconut oil has been concluded by GC-MS. The result of analysis in ferment coconut oil yiels four kinds of fatty acid that are (1). Laurate acid (methyl dodekanoat) 39,13%, (2). Myristate acid (methyl tetradekanoat) 13,78%, (3). Palmitate acid (methyl heksadekanoat) 6,60%, and (4). Oleate acid (Methyl 9-oktadekanoat) 4,81%. While traditional coconut oil yiels five kinds of fatty acid, that are (1). Laurate acid (methyl dodekanoat) 44,83%, (2). Myristate acid (methyl tetradekanoat) 22,83, (3). Palmitate acid (methyl heksadekanoat) 12,82%, (4). Oleate acid (Methyl 9-oktadekanoat) 11,16%, and (5) Stearate acid (Methyl oktadekanoat) 3,90%. Stearate acid is none in ferment coconut oil because it lost used by khamir. Traditional coconut oil is better than ferment coconut oil in number and kind of fatty acid. But from the physic character like number of oil, time cook, and face, ferment coconut oil is better. Method made is influence to compound of fatty acid. In other research, it’s important to find the optimal condition procces for khamir fermentation. People may eat traditional coconut oil cos it have some fatty acid that important for human body